2020
DOI: 10.1021/jacs.0c01758
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Based Bioorthogonal Nanocatalysts for the Treatment of Bacterial Biofilms

Abstract: Bioorthogonal catalysis offers a unique strategy to modulate biological processes through the in situ generation of therapeutic agents. However, the direct application of bioorthogonal transition metal catalysts (TMCs) in complex media poses numerous challenges due to issues of limited biocompatibility, poor water solubility, and catalyst deactivation in biological environments. We report here the creation of catalytic "polyzymes", comprised of self-assembled polymer nanoparticles engineered to encapsulate lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 50 publications
0
101
0
Order By: Relevance
“…The high antimicrobiala ctivity is achieved at concentrations that do not compromise the fibroblast cell viability. [134]…”
Section: Tandemazide Reduction and Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…The high antimicrobiala ctivity is achieved at concentrations that do not compromise the fibroblast cell viability. [134]…”
Section: Tandemazide Reduction and Cleavagementioning
confidence: 99%
“…Accordingly, these nanosystems exhibited excellent catalytic efficiency for the activation of fluoroquinolone prodrugs such as pro‐moxifloxacin or pro‐ciprofloxacin within biofilms of E. coli or Pseudomonas aeruginosa . The high antimicrobial activity is achieved at concentrations that do not compromise the fibroblast cell viability [134] …”
Section: Bond Cleavage Reactionsmentioning
confidence: 99%
“…Another common stimulus to trigger nanoparticle aggregation is pH, a property can be used to target acidic microenvironments such as those found in tumors or bacterial biofilms [ 125 , 126 , 127 , 128 ]. Early work by Kim demonstrated that nanoparticles can respond to pH changes and form aggregates [ 129 ].…”
Section: Modulating Nano-bio Interactions Through Stimuli-responsive Npsmentioning
confidence: 99%
“…We report here the fabrication of a ruthenium‐based “polyzyme” employing a poly(oxanorbornene imide) scaffold [ 48 ] for in vitro anti‐cancer demonstration. The polymeric scaffolds employed feature cationic hydrophobic imide functionalization, imparting both water solubility and inducing polymer self‐assembly around the ruthenium TMCs.…”
Section: Introductionmentioning
confidence: 99%